Determinação do índice de qualidade da água tratada distribuída aos municípios do estado de Goiás - Fernandes, Neemias Cintra (2013)
Individual evaluation of the results of each one of the physical, chemical and biological parameters monitored for quality control of water distributed to the population is an activity hampered by the great diversity and quantity of data generated by the analysis. Determinations of water quality indices (WQI) has been used to convert a series of data of water quality in a single number, able to represent a simple and objective way, the water quality as whole. Aimed at obtaining WQIs of the 224 municipalities in Goiás, that have supply systems operated by state sanitation company (SANEAGO), this study investigated data on physical-chemical and microbiological tests, performed according to methods described in Standard Methods, in samples supply water collected during two years (oct., 2011 to aug., 2013) and, by the Canadian method known as CWQI (Canadian water Quality Index), determined the WQI of each one of 224 municipalities evaluated, and also determined the WQI referent to geographical microregions and mesoregions of Goiás, allowing the spatialization of results in maps of the state of Goiás. The evaluation concluded that 97.8% of municipalities in Goiás, which water supply systems are operated by SANEAGO, have WQI categorized as 'Excellent' or 'Good', compared with 2.2% of municipalities categorized as 'Regular' or ‘Bad’. The spatial distribution of the results led to the conclusion that, at the end of the study period, the mesoregion Center classified as 'Excellent' in terms of WQI, while mesoregions East, Northwest, North and South are classified as 'Good'.